Magnetic and superconducting properties of FeSe₁–xTex (x≃0, 0.5, and 1.0) - Fedorchenko, A.V.; Grechnev, G.E.; Desnenko, V.A.; Panfilov, A.S.; Gnatchenko, S.L.; Tsurkan, V.V.; Deisenhofer, J.; Krug von Nidda, H.-A.; Loidl, A.; Chareev, D.A.; Volkova, O.S.; Vasiliev, A.N. (Физика низких температур, 2011)
Magnetization studies for FeSe₁–xTex (x≃0, 0.5, and 1.0) compounds were carried out in magnetic fields up to 50 kOe and in the temperature range 2–300 K. The superconducting transition was observed at Tc≃8 K and 13.6–14.2 K in FeSe₀.₉₆₃ and FeSe₀.₅Te₀.₅, respectively. For the most samples, a nonlinear behavior of the magnetization curves in the normal state gives evidence of a commonly observed substantial presence of ferromagnetic impurities in the compounds under study. By taking these impurity effects into account, the intrinsic magnetic susceptibility χ of FeSe₀.₉₆₃ and FeSe₀.₅Te₀.₅, and FeTe was estimated to increase gradually with Te content. For FeTe a drastic drop in χ(T) with decreasing temperature was found at TN≃70 K, which is presumably related to antiferromagnetic ordering. To shed light on the observed magnetic properties, ab initio calculations of the exchange enhanced magnetic susceptibility are performed for FeSe and FeTe within the local spin density approximation.